Work pressure and job dissatisfaction: Challenges in Danish general practice - Anne Sophie Oxholm; Thomas Allen; Dorte Gyrd-Hansen; Dorte Ejg Jarbøl; Rikke Vognbjerg Sydenham; Line Bjørnskov Pedersen (University of Oslo, 2022)
A main objective of the Nordic healthcare systems is to deliver timely and equal access to high-quality healthcare to the entire population. Health care providers, such as general practitioners (GPs), may therefore experience pressure to deliver care from both the health authorities and patients. However, if GPs' gains do not outweigh their costs of providing the demanded care, it may lead to job dissatisfaction and thereby potentially to poorer quality of care. This study contributes to the literature by estimating the association between different sources of experienced work pressure and job dissatisfaction among GPs. We use data from a nation-wide survey of Danish GPs distributed in 2019. The study includes six items covering GPs' experienced work pressure, which we categorise based on the degree to which they are related to demands from either patients or health authorities. Using a series of ordered logit models with a rich set of explanatory variables, we estimate the association between the pressure measures and GP job dissatisfaction. We find that GPs reporting high or considerable work pressure have an increased likelihood of also reporting job dissatisfaction. However, we find considerable heterogeneity in this relationship across different sources of work pressure as well as across GP, practice, and area characteristics. For example, the relationship between pressure from patients' demands for consultations and job dissatisfaction is stronger among GPs practicing in areas with an undersupply of GPs. Solo practitioners, who cannot share their administrative burdens with colleagues, experience a stronger association between pressure from the health authorities and job dissatisfaction. Policymakers should consider this heterogeneity when implementing new schemes and organisational structures affecting GPs' work pressure. Published: Online January 2022.